Identifying six-year cycle in GRACE total water storage time-series with a model test algorithm and assessing its influence on trend estimates in Turkiye region over a twenty year period - Gunes, Ozge; Aydin, Cuneyt (ELSEVIER SCI LTD, 2025)
The Gravity Recovery and Climate Experiment (GRACE) satellite mission, launched in 2002, has significantly advanced our understanding of temporal variations in Earth's gravity field. Its remarkable sensitivity to hydrological changes on land and fluctuations in ocean bottom pressure has led to its widespread use in hydrology, geodesy, glaciology, and oceanography. Hydrological variations on Earth's surface are monitored through total water storage (TWS) anomalies expressed in equivalent water thickness. It has been reported that a TWS time-series consists of a long-term periodic signal, termed 6-year cycle. We examine this cycle in the TWS time-series of global mascon solutions provided by the Goddard Space Flight Center (GSFC), covering the period from April 2002 to May 2023. To identify this cycle, we propose an algorithm that searches for the best fitting periodic signal among the possible ones to the TWS time-series based on the F-model test. This algorithm is proven to be successful with an error of around 1 year even if the time-series data is burdened with the random walk noise. Applying this procedure to the GSFC mascon TWS time-series, we identified an additional signal with a global mean period of 6.4 years. We further investigated its influence on trend rate estimates over the Turkiye Region. Enhancing harmonic regression model with the identified periodic signals in the region reduces the energy of the colored noise in the data as well as trend rate uncertainty by up to 33 %. This is a significant improvement of considering the 6-year cycle while investigating the TWS signal in the region. (c) 2025 COSPAR. Published by Elsevier B.V. All rights are reserved, including those for text and data mining, AI training, and similar technologies.
Keywords: GRACE; Hydrological Variation; Additional Signal; 6-year cycle; TWS; LENGTH; Engineering; Astronomy & Astrophysics; Geology; Meteorology & Atmospheric Sciences